Ireland and race : ideas, intellectuals and identities - Moriarty, Elaine (Trinity College (Dublin, Ireland). Department of Sociology, 2007)
This dissertation offers an exploration of the processes involved in the construction of discourses of Irishness and otherness as it relates to migration and anti racism in Ireland between 1990 and 2005. In doing so, I propose that a routinisation of racialisation has occurred through the re-conceptualisation of Irishness and dialectically through the re-shaping of how belonging is constituted in Ireland. By combining processes of theoretical conceptualisation and problematisation with documentary analysis, I map the field of Irishness as it relates to migration and anti racism through a qualitative research process. In developing a research agenda for this dissertation, I posit a dialectical matrix of routinised practices, discursive formations and systemic rules and resources. In articulating such a process of social constitution, I argue that it occurs through a dialectic involving two key processes: routinisation and enacted conduct. Ultimately I argue that this produces what I refer to as public culture and its racialised regimes of representation. Such an approach makes possible an exploration of the relationships between disparate government laws and policies, everyday gossip and urban legends, media articles, and voluntary organisation activities in the constitution of Irishness and otherness with regard to migration and anti racism. Through an analysis of the discourses and representations of Irishness and otherness within sites of intellectualism including media, government, institutionalised anti racism and visual culture, the dialectical approach enables me to focus on the intersections across these sites which serve to illuminate the co-construction of belonging in Ireland.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin